Comparison of the structural diversity between a humid and subhumid tropical forest in Tabasco, Mexico - Martínez-Sánchez, José Luis (Instituto de Ecología, A.C., 2016)
Due to the fact that tree size can significantly influence community structure, and thus diversity, structural diversity indices which incorporate DBH and total tree height can be more accurate estimators than the classic diversity indices. The structural diversity of a tropical humid forest (THF) and a tropical sub-humid forest (TSF), in Tabasco, Mexico, was compared using eight structural indexes that estimate community basal area sorted by DBH and tree height classes. The species, DBH and total tree height of trees > 10 cm DBH were determined. The structural indices were statistically compared between the two communities. The TSF presented 27 species, 211 trees and 129 palms ha-1, a mean DBH of 28.0 cm and 9 trees > 20 m height. The THF presented 66 species and 591 trees ha-1, a mean DBH of 21.2 cm and 36 trees > 20 m height. The structural indices of the THF (2.76 – 6.737) were significantly higher than those of the TSF (2.345 – 4.978). The Gini indices of the THF (0.61 and 0.494) indicated that trees were more heterogeneous in size (diameter and height) than those of the TSF (0.583 and 0.419). The structural indices therefore evaluate species diversity and community structural diversity in a more complete way, with the THF presenting higher structural diversity than TSF, which suggests the value of their use within tree vegetation studies.